A systematic review of herbal medicinal products for the treatment of menopausal symptoms - L Kashani; FS Bathaei; M Ojaghi; M Bathaei; S Akondzadeh (Institue of Medicinal Plants, ACECR, 2004)
Many women are interested to use complementary and alternative medicines for relief from their menopausal symptoms. The prevalence of herbal medicinal product use among menopausal women highlights the need for investigation into these interventions. The goal of this study was to evaluate the benefit of herbal medicinal products for the treatment of menopausal symptoms by performing a systematic review of clinical trials. Literature searches of four computerized databases were done to identify randomized clinical trials of herbal medicinal products for the treatment of menopausal symptoms. Manufacturers of herbal products were contacted, and our own files were also searched. There were no restrictions on the language of publication. Trials were considered if the outcome measures related to the physical or psychological impact of menopause, whether by compendium scores, questionnaires, or womenchr('39')s symptom diaries, excluding studies describing artificially induced menopause. This review was not concerned with biochemical or pathological data. Eighteen randomized clinical trials that fit our criteria were identified. These studies investigated black cohosh (n = 4), red clover (n = 4), kava (n = 3), dong quai (n = 1), evening primrose oil (n = 1), ginseng (n = 1), and combination products (n = 4). Trial quality was generally good, with 16 of 18 studies scoring 3 or more (maximum 5) on the Jadad Scale. There is no enough evidence for any herbal medical product in the treatment of menopausal symptoms. However, the evidence for black cohosh is promising.The studies involving red clover show it may be of benefit for more severe menopausal symptoms. There is some document for the use of kava, but safety concerns mean this herbal product is not a therapeutic option at present.